Analisis Kesalahan Terjemahan Hadis-Hadis Kitab al-Jami’ di dalam Bulughul Maram Karya Moh. Machfuddin Aladip - Anhar, Khairul; Rahimah, Rahimah; Lubis, M. Husnan (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This study aims to reveal the translation errors that occurred in the translation of the hadiths of al-jami' in the book Bulughul Maram by Moh. Macfuddin Aladip and explained the factors that these errors occurred. There have been many studies on the translation of religious texts. This is very important to do in order to control the results of the translation and understanding of the people's religions on these religious texts. In this study, an assessment and analysis of the translation of the book Bulughul Maram Min Adillatil Ahkam by Moh. Machfuddin Aladip, in the chapter of Kitab al-jami '. In revealing the errors that occur in the translation, a comparison technique between the source language and the target language is used by paying attention to the aspects of sharf, nahw and dilalah science. From this study found fatal errors in the translation of several hadiths studied in the book Bulughul Maram Min Adillatil Ahkam by Moh. Machfuddin Aladip, in the chapter of Kitab al-jami'. In addition, the errors that occur are caused by the following factors: (1) lexical improper matching, (2) adding words or phrases to more than words in the source text, (3) shifts that occur at the word level, (4) Elimination of equivalent words and phrases, (5) Identifying words in the source language.